Quantitative In Situ Visualization of Thermal Effects on the Formation of Gold Nanocrystals in Solution. Issue 38 (2nd August 2021) - Khelfa, Abdelali; Nelayah, Jaysen; Amara, Hakim; Wang, Guillaume; Ricolleau, Christian; Alloyeau, Damien
Abstract: Understanding temperature effects in nanochemistry requires real‐time in situ measurements because this key parameter of wet‐chemical synthesis simultaneously influences the kinetics of chemical reactions and the thermodynamic equilibrium of nanomaterials in solution. Here, temperature‐controlled liquid cell transmission electron microscopy is exploited to directly image the radiolysis‐driven formation of gold nanoparticles between 25 ° C and 85 ° C and provide a deeper understanding of the atomic‐scale processes determining the size and shape of gold colloids. By quantitatively comparing the nucleation and growth rates of colloidal assemblies with classical models for nanocrystal formation, it is shown that the increase of the molecular diffusion and the solubility of gold governs the drastic changes in the formation dynamics of nanostructures in solution with temperature. In contraction with the common view of coarsening processes in solution, it is also demonstrated that the dissolution of nanoparticles and thus the Ostwald ripening is not only driven by size effects. Furthermore, visualizing thermal effects on faceting processes at the single nanoparticle level reveals how the competition between the growth speed and the surface diffusion dictates the final shape of nanocrystals. Abstract : How temperature affects the formation of gold nanoparticles in water is revealed by liquid‐phase transmission electron microscopy. Thermal effects on the nucleation and growth rates of the colloidal assemblies match with the classical models for nanoparticle formation but the direct observation of single nanoparticle dynamics provides new in situ insights into the atomic‐scale mechanisms governing the size and shape of nanostructures.